Circulating fibroblast growth factor-21, Omentin-1, and betatrophin and their association with metabolic parameters in Saudi adolescents post 12-month lifestyle change program - Mona M. Alenazi; Shaun Sabico; Abdullah M. Alnaami; Kaiser Wani; Syed D. Hussain; Nasser M. Al-Daghri (BMC Pediatrics)
Abstract Background Fibroblast growth factor-21 (FGF21) and omentin-1 have been recognized as potent antidiabetic agents with potential hepatoprotective activity. The aim of this study was to evaluate the associations between betatrophin, hepatic FGF21 and omentin-1 as predictive markers of insulin resistance in adolescents who underwent a 12-month lifestyle change intervention program. Methods Prospective data of 218 Saudi adolescents (45 normal and 77 overweight, and 96 obese) (mean age = 15.1 ± 1.5 years and mean BMI = 35.1 ± 6.6 kg/m2) who participated in a 12-month lifestyle modification program were included. Baseline and follow-up data on anthropometrics and clinical data were collected. Serum levels of betatrophin, omentin-1, FGF-21 and 25(OH)D were assessed using commercially available assays. Analysis and comparisons were done according to varying levels of body mass index (BMI) and glycemic status. Results Results showed that betatrophin level decreased in the obese and prediabetic groups (p = 0.03, p = 0.002 respectively). There was a significant decrease in BMI in obese and overweight participants after the 12-month lifestyle modification program [35.1 ± 6.6 & 33.1 ± 7.5 and 26.6 ± 1.5 & 25.6 ± 2.3, p < 0.05 and p < 0.01 respectively]. Follow-up omentin1 was significantly elevated in overweight and obese individuals but no significant difference in omentin-1 in prediabetic group at follow-up was observed (p > 0.05). Conclusion We concluded that betatrophin levels had an inverse association with metabolic biomarkers omentin-1, FGF-21, and 25(OH)D after a 12-month lifestyle modification program. A healthy diet and exercise are associated with decreased betatrophin levels and improving glucose tolerance.